Sustainable Quality Management: A Practical Approach to Balancing Profitability and Environmental Responsibility - Alrahmani, Dr. Abdulrahman (The Gulf Economist, 2025)
This study aims to investigate a pragmatic method for reconciling profitability with environmental responsibility in the context of sustainable quality management. The research employs a quantitative methodology, using a survey-based framework to gather data from firms that are actively engaged in sustainable quality management techniques. The study utilizes a questionnaire as a method of measurement for the knowledge application on sustainability in business processes. Our sample will include 200 respondents of Basra Oil Company to achieve a diverse and representative sample of perspectives. The objective of the research is to examine the trends, patterns and relationship between sustainable quality management practices and profitability while analyzing the data collected in survey. This research can improve our understanding of how businesses may thrive by balancing environmental responsibility with profit-seeking behavior and the determinants that enable or impede such behavior. The study suggests organizations enact holistic sustainability plans and integrate environmental matters into their quality management systems to improve profits without sacrificing sustainability